2015
DOI: 10.1007/s11010-015-2457-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of procyanidin B1 on LPS-treated THP1 cells via interaction with the TLR4–MD-2 heterodimer and p38 MAPK and NF-κB signaling

Abstract: Anti-inflammatory effects of procyanidin B1 have been documented; however, the molecular mechanisms that are involved have not been fully elucidated. Molecular docking models were applied to evaluate the binding capacity of lipopolysaccharide (LPS) and procyanidin B1 with the toll-like receptor (TLR)4/myeloid differentiation factor (MD)-2 complex. LPS-induced production of the proinflammatory cytokine tumor necrosis factor (TNF)-α in a human monocyte cell line (THP1) was measured by ELISA. mRNA expression of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 35 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Inhibiting TLR4 signaling has received considerable attention in the regulation of innate immune response. LPS-activated TLR4 regulates the expression and translocation of NF-κB 27 . Interferon-γ (IFN-γ) helps in activating anti-microbial and anti-tumor lymphocytes to regulate the proliferation and differentiation of biomolecules 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibiting TLR4 signaling has received considerable attention in the regulation of innate immune response. LPS-activated TLR4 regulates the expression and translocation of NF-κB 27 . Interferon-γ (IFN-γ) helps in activating anti-microbial and anti-tumor lymphocytes to regulate the proliferation and differentiation of biomolecules 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that MAPKs are involved in many biological processes, including inflammation, apoptosis, cell growth, and differentiation, and are particularly activated in response to cytokines and stress [41]. In addition, MAPK signaling cascades are activated by LPS through binding of LPS to the TLR4 receptor, which is a critical factor in the signal transduction pathways involved in controlling inflammatory mediators in macrophages [42]. Several lines of evidence have shown that the activation of ERK1/2, p38, and JNK is involved in the regulation of AP-1 activity by increasing transcription [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested that hexameric PACs inhibit bile acid-induced activation of ERK1/2 and p38 MAPKs in intestinal epithelial cells by a lipid raft-dependent effect involving inhibition of NADPH oxidase (NOX) [165]. More recently, a molecular docking analysis indicated that procyanidin B1 may bind to the TLR4/MD-2 complex and be able to act as a competitive antagonist of LPS [166]. This effect was associated with the inhibition of the LPS-induced phosphorylation of p38 MAPK and activation of NF-κB signaling in THP1 (human monocyte) cells.…”
Section: Modulation Of Signaling Transduction Pathwaysmentioning
confidence: 99%